Composition of Longline Fishing Catches in Sungai Sembilan Waters, Bangsal Aceh District, Dumai City, Riau Province - Adha, Dwicha Addiva; Zain, Jonny; Isnaniah, Isnaniah (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The longline fishing gear in the Bangsal Aceh District is a secondary fishing gear from the pengerih fishing gear, the Bangsal Aceh anglers use the longline fishing gear when they are free or when anglers only want to use it. This study aims to determine the construction of longline fishing gear and determine the basic composition of longline catches using bait that is often used. The research method used is a survey method. The data collected starts from supplies, ship condition, condition of fishing gear, data on fish species, fish weight, and the number of individual fish, which are then analyzed by calculating the effort of the hook rate, and the catches obtained. Then analyzed descriptively by defining the main catch and bycatch. From the results of the research conducted for two weeks, the catch consisted of three types, namely giant catfish, sagor, and stingrays. Stingrays were the heaviest fish weighing 57.8 kg (80.38%), followed by giant catfish with 13.6 kg (18.9152%), and sagor with 0.5 kg (0.69541%). Meanwhile, according to individuals, the most commonly found fish were 11 giant catfish (64.7%), followed by 5 stingrays (29.4118%), and 1 sagor (5.88235%). Meanwhile, according to individuals, the most commonly found fish were 11 giant catfish (64.7%), followed by 5 stingrays (29.4118%), and 1 sagor (5.88235%). Meanwhile, according to individuals, the most commonly found fish were 11 Giant catfish (64.7%), followed by 5 stingrays (29.4118%) and 1 sagor (5.88235%).